-4(4f-2)=-18f

Simple and best practice solution for -4(4f-2)=-18f equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -4(4f-2)=-18f equation:



-4(4f-2)=-18f
We move all terms to the left:
-4(4f-2)-(-18f)=0
We multiply parentheses
-16f-(-18f)+8=0
We get rid of parentheses
-16f+18f+8=0
We add all the numbers together, and all the variables
2f+8=0
We move all terms containing f to the left, all other terms to the right
2f=-8
f=-8/2
f=-4

See similar equations:

| 7b+12=4.2 | | T+46=4t+16 | | |8+10x|+4=10 | | 0=3x^2+14x-24 | | 0=-16x^2-32x+110 | | -16-4(-5m+11)=17m | | 5v=v+33 | | 2t-16=3t-32 | | 7x+200=11x+80 | | 19x-12=8x-23 | | (t)=-16t^+50t+3.5 | | 8x+6=5x–12 | | 20x+16=0 | | 72+c-27=13c+9 | | +2x+6=20 | | 18u-6=16u | | X÷4=2x-16 | | 10t=-120 | | 7x2x-7=35 | | S+29=3s-32 | | X+19+3x=-5-13x-11 | | S+29=3s-33 | | +2x+5=3 | | 7|2x-7|=35 | | F(-5)=-4c+16 | | 27z=54 | | F(4)=-4c+16 | | 2t+23=t+41 | | 5(5x+84)=4(x+63) | | U=2u-19 | | g·3=0.9 | | 8x-2=5x-13 |

Equations solver categories